Formulasi Krim Ekstrak Buah Mengkudu (Morinda citrifolia L.) sebagai Antioksidan - Dewi Ekowati; Dwi Ningsih (Jurnal Farmasi Indonesia, 2014)
Noni (Morinda citrifolia L.) has long been known as a nutritious plants. Noni has known contain ascorbic acid and Î² - carotene as an antioxidant function. The purpose of this research is to create a cream preparation with qualified physical properties and stability of extracts of noni as an antioxidant. The noni fruit extract was made cream in three formula with concentrations of 5%, 7,5%, and 10%. The physical properties and stability testing of the cream were viscosity, dispersive power, pH and viscosity changes. Antioxidant activity of noni fruit extract cream was tested by DPPH method. The results showed that the noni fruit extract could made cream until concentration of 10%. The noni fruit extrac creams had antioxidant activity. Formula III contained noni fruit extract was the best formula which had antioxidant activity with IC50 value of 69,61 mg/mL.